The result of in vitro fertilazation of Mongolian sheep oocytes (Mongolian Journal of Agricultural Sciences, 2019)
The effects of astaxanthin (Ax) were tested in ovine oocytes during the maturational culture. Oocytes were cultured for 22 hours in with or without 500 ng/ml Ax. Oocytes and embryos were cultured in the multi-incubator with 39°C till the development stage of blastocysts during 7 days. After maturational culture, the embryos transferred to the synchronized recipients.Fertilization rate was similar in Ax-treated oocytes and in non-treated oocytes. The development of blastocysts in the Ax-treated oocytes tended to be higher than in non-treated oocytes (P=0.06). These results indicate that Ax treatment improves the developmental competence of ovine oocytes. The first lamps were born in Mongolia using the method of in vitro culture.Монгол хонины өндгөн эсийг in vitro орчинд үр тогтоосон дүн Бид хонины өндгөн эсийг in vitro орчинд үр тогтооход астаксантин бодис хэрхэн нөлөөлөхийг судлав. Өндгөн эсийг 22 цагийн турш 500 ng/ml астаксантин (Ax) агуулсан болон агуулаагүй орчинд бойжуулж үр тогтоолыг хийв. Үр тогтсон хөврөлийн 39оС мульт-инкубаторт 7 хоног байлгаж бластоцист шат хүртэл нь өсгөвөрлөсний дараа тээгч хээлтэгчид шилжүүлэн суулгав. Астаксантин агуулсан болон агуулаагүй орчинд үр тогтолтын үр дүн бодитой ялгаа байхгүй байв. Харин бластоцистийн шат хүртэл хөгжих үед астаксантин бүхий орчинд өсгөвөрлөсөн хөврөлийн хөгжил астаксингүй орчныхоос илүү байв (P=0.06). Энэ нь үр тогтсоны дараа хөврөлийн цаашдын хөгжилд астаксантин эерэг нөлөөтэй болохыг илэрхийлж байна. Монгол орны нөхцөлд анх удаа in vitro орчинд өсгөвөрлөсөн хөврөлийн гаралтай хурга гаргаж авав.Түлхүүр үг: өндгөн эс, морул, бластоцист, хөврөл, антиоксидант